From Practice to Print: Women Crafting Authority at the Margins of Orthodox Medicine - Carlyle, Margaret (Mémoires du livre / Studies in Book Culture, 2014)
This article analyzes how a category of women possessing medical secrets known as “femmes à secrets” entered commercial medicine in mid- to late-xviiith-century Paris. It reads sources including remedy patents and printed publicity with a view to exploring women’s agency in producing and peddling medical products and services within the burgeoning marketplace. It shows how this form of “fringe” practice provided a unique forum where women cultivated their authority outside of learned medicine while also interacting with it. In doing so, the article displaces traditional narratives which position charlatans and quacks as the primary practitioners who colonized the margins of medical practice. Instead, it provides an account of women as examples of the dynamic “fringe” practitioners who strove to prove their genuine authority across a variety of domains. By bringing their practice to print, enterprising women succeeding in staking out their claim to expertise in a growing and increasingly consumerist, legislated, and policed medical milieu, where the boundaries between “expert” and “amateur” knowledge traditions were becoming increasingly blurred.